Administration of Moringa oleifera seeds ethanol extracts cream increased neovascularization and fibroblasts cell, but did not increase epithelialization in wound healing process of wistar rats (Rattus norvegicus) - Golda Bernadet Lemewu; I Gusti Made Aman; Anak Agung Gede Putra Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: The aging process causes a decrease in organ function like wound healing. Moringa seed extract contains various compounds that can accelerate wound healing. The purpose of this study was to prove that administration of Moringa oleifera can accelerate wound healing process. Methods: This study used a randomized post-test control group design. Subject were 28 rats (Rattus norvegicus), Wistar strain, which were divided into 4 groups (n = 7). The P0(4) and P0(8) group was given placebo for 4 and 8 days, the P1(4) and P1(8) group was given Moringa seed extract cream for 4 and 8 days. All group were given oral amoxicillin 3x10mg/day. Skin samples were biopsied at the wound site. Results: The results showed that the average neovascularization in P0(4) group was 3.57±1.13, P1(4) = 7.71±2.06, P0(8) = 4.14±1.22, and P1(8) = 8.00±1.41 (p < 0.001). The number of fibroblast cells in the P0(4) = 39.4±6.19, P1(4) = 64.3±6.08, P0(8) = 47.0±16.2, and P1(8) = 75.7±17.1 (p < 0.001). The epithelium thickness of the P0(4) = 39.1±15.9 μm, P1(4) = 33.8±3.50 μm, P0(8) = 28.9±11.5 μm, and P1(8) = 38.9±21.5 μm (p> 0.05). The epithelium gap of the P0(4) = 1239±1079 μm, P1(4) = 380±441 μm, P0(8) = 838±1072 μm, and P1(8) = 1153±594 μm (p> 0.05). Conclusion: It can be concluded that administration of Moringa oleifera seeds ethanol extracts cream increased neovascularization and fibroblast cell, but did not increase epithelialization in wound healing process of wistar rats.